Long-term strength training effects on change-of-direction sprint performance - Keiner, M.; Sander, A.; Wirth, K.; Schmidtbleicher, D. (The Journal of Strength and Conditioning Research, 2014)
The requirement profiles for sports such as soccer, football, tennis, and rugby demonstrate the importance of strength and speed-strength abilities, in addition to other conditional characteristics. During a game, the athletes complete a large number of strength and speed-strength actions. In addition to the linear sprints, athletes perform sprints while changing the direction (change-of-direction sprint [COD]). Therefore, this study aims to clarify the extent to which there is a strength training intervention effect on COD. Further, this investigation analyzes the possible correlations between the 1-Repetition Maximum/body mass (SREL) in the front and back squats and COD. The subjects (n = 112) were at pretest between 13 and 18 years of age and were divided into 2 groups with 4 subgroups (A = under 19 years of age, B = under 17 years of age, and C = under 15 years of age). For approximately 2 years, 1 group (control group [CG]) only participated in routine soccer training, and the other group (strength training group [STG]) participated in an additional strength training program with the routine soccer training. Additionally, the performances in the COD of 34 professional soccer players of the first and second divisions in Germany were measured as a standard of high-level COD. For the analysis of the performance development within a group and pairwise comparisons between 2 groups, an analysis of variance with repeated measures was calculated with the factors group and time. Relationships between the COD and SREL were calculated for the normal distributed data using a plurality of bivariate correlations by Pearson. Our data show that additional strength training over a period of 2 years significantly affects the performance in the COD. The STG in all subcohorts reached significantly (p < 0.05) faster times in the COD than did the CG. The STG amounted up to 5% to nearly 10% better improvements in the 10-m sprint times compared with that of the CG. Furthermore, our data show significant (p < 0.05) moderate to high correlations (r = -0.388 to -0.697) between the SREL and COD. Our data show that a long-term strength training improves the performance of the COD. Therefore, a long-term resistance training is recommended as early as in childhood and adolescence.